Rising from the ashes : survival, sovereignty, and Native America - Willard, William, 1926-2016; Marshall, Alan G. (Alan Gould); Pearson, J. Diane, 1941- (University of Nebraska Press, 2020)
"Rising from the Ashes explores continuing Native American survival, contemporary life, and sovereignty, with a focus on the life of the Numipu (Nez Perce) anthropologist Archie M. Phinney."--